Phytochemical and pharmacognostic evaluation of leaves of Pongamia pinnata L. (Fabaceae) - Menpara, Disha; Chanda, Sumitra (Pharmacognosy Communications)
Objective: The objective of this study was to carry out phytochemical and pharmacognostic evaluation of leaves of Pongamia pinnata L. (Fabacea). Method: The present study provides pharmacognostic, physicochemical and phytochemical details of the leaves of P. pinnata. Macro and microscopic evaluation and WHO recommended parameters were followed in the study. Results: The macroscopic study showed that the leaf was ovate or elliptic with smooth margins, short petiole, alternate imparipinnate, hairless, acuminate at apex, rounded to cuneate at base and slightly thickened. Microscopic study revealed collateral, closed vascular bundles, trichomes, paracytic stomata, xylem vessels and prismatic calcium oxalate crystals. Physiochemical analysis of leaf showed total ash, water soluble ash and acid insoluble ash as 8.33±0.31, 2.33±0.36 and 0.5±0.0 %w/w respectively. Preliminary phytochemical screening showed the presence of alkaloids, flavonoids, tannins, triterpenes, cardiac glycosides, steroids and saponins. Conclusions: The results of this study can serve as valuable source of information for identification of this plant for future investigation and applications.
Keywords: Pongamia pinnata; pharmacognostic; phytochemical; physicochemical; leaf